Thèmes en contexte - JABRA, George (Proche-Orient Chrétien, 2025)
For the first time, the Diocese of the Episcopal/Anglican Church in Jerusalem and the Middle East held an ecclesiastical juridical conference in the Dead Sea area in Jordan from April 8 to 10, 2024. The main reason for organizing this conference was to discuss the laws governing personal affairs in the Diocese and to revisit the regulations that have been applied in church courts since 1976. Several factors motivated this discussion. [...]